RELIGIOUS FUNDAMENTALISM AND INDIAN SECULARISM: THE PRESENT CRISIS - M.M. Thomas (Journal of Dharma, 1994)
Indian secularism emerged as a basic political ideology in the course of the Indian national struggle for independence. It emerged as the concept of Secular Nationalism in opposition to the nationalism based on the interests of one or the ether of the religious communities, therefore also called communalism. The Hindu Nationalism with its goal of "Akhand Hindustan" and drawing its strength from Hindu ’revivalism appeared with militancy in the latter half of the first decade of the century in the Congress in opposition to the weakness of the Liberal Nationalism of the earlier period. With its weakening in the Congress it found organized expression in the Hindu Mahasabha and later in the RSS; and the two-nations theory that India consists of the Hindu and theIslamic nations which is to be separated at independence found organized expression in the Muslim League.